Rarely pure and never simple: Extracting the truth from self-reported data on substance use - Stephen Pudney (Centre for Microdata Methods and Practice (cemmap), 2007)
We consider the misreporting of illicit drug use and juvenile smoking in self-report surveys and its consequences for statistical inference. Panel data containing repeated self-reports of 'lifetime' prevalence give unambiguous evidence of misreporting as 'recanting' of earlier reports of drug use. The identification of true initiation and reporting processes from such data is problematic in short panels, whilst more secure identification is possible in panels with at least five waves. Nevertheless, evidence from three UK datasets clearly indicates serious underreporting of cannabis, cocaine and tobacco use by young people, with consequent large biases in statistical modelling.
Keywords: C41; D12; I19; 330; illicit drugs; smoking; misreporting; measurement error; nonparametric identification; OCJS; BCS70; BHPS; Drogenkonsum; Rauchen; Jugendliche; Statistischer Fehler; Schätzung; Großbritannien